PEDULI DAN PENCEGAHAN COVID-19 DI RT. 009, RW. 016, KELURAHAN BAKTI JAYA, KECAMATAN SUKMA JAYA, DEPOK - yelvi, yelvi (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2020)
COVID-19 in Indonesia was first discovered in Depok, West Java. Two Depok Residents were declared positive COVID-19 on March 2, 2020. Since the announcement of the first case. Depok is now a city in West Java Province with the most COVID-19 positive cases. To suppress the spread of COVID-19, the Depok city government imposed large-scale social restrictions (PSBB) on April 15, 2020. The public’s impact is strongly felt due to the enactment of PSBB in terms of the economy. Many people have to lose their jobs. Public awareness in maintaining cleanliness and health is also still lacking due to the public’s inability to buy masks and hand soap whose prices soar. The Jakarta State Polytechnic Civil Engineering Department’s Road and Bridge Design Engineering Program (TPJJ) is motivated to participate in assisting communities affected by COVID-19 by holding community service activities. Sukmajaya sub-district is the area in Depok that is most infected with COVID-19. Based on this, TPJJ Study Program will assist in providing public sinks, the distribution of masks, hand soap, and food at RT 009 RW 016 Bakti Jaya subdistrict Sukmajaya Sub-District, Depok. It is hoped that this activity can reduce the spread of COVID-19 and can ease the burden on people who are experiencing economic hardship.